4 - Surviving a Rabid Economy: The Current Cash Crisis and its Threat to Security and Governance in the Monetary Sector in Zimbabwe - Gudhlanga, Enna Sukutai; Madongonda, Angeline Mavis (Africa Development, 2019)
Economic instability and the suffering of ordinary Zimbabweans is what prompted the writing of this article. To overcome the prevailing abject poverty, Zimbabweans have come up with all sorts of strategies to survive the ravages of the wobbly economic system characterised by the prevailing cash crisis. The aim of this article was to find out the different ways used by Zimbabweans to survive the harsh economic environment. Informal interviews were conducted with 10 selected ordinary citizens in Harare’s Central Business District who have been hard hit by the current cash crisis and have devised ways of survival. The snowballing technique was used to identify the respondents in the study. Findings of the study revealed that Zimbabweans are engaging a myriad of strategies of surviving the current status quo. Of concern, in the findings was the magnitude of shady dealings involved as people try to get hold of the ever-elusive dollar. While most of the illicit dealings are done in informal settings, productivity levels in the formal sector appear to be suffering a knock, with productive time lost in search of hard cash. It is recommended that consultations with the general populace be done before introducing monetary reforms in any country; that the government should curb informal and illicit monetary exchanges which continue to be a threat to both governance and national security; and that stringent measures to outlaw corruption from all sections of society and open lines of communication be created that register the people’s discontent with the current monetary policies and systems. The study may not be exhaustive but it gives an understanding of what the larger population is grappling with.